GABA, glutamate, glutathione, and central pain in people with knee osteoarthritis: a pre- and post-knee replacement study - Armstrong, Mataea (Peer Beyond Graduate Research Conference, 2025)
KOAPAIN2 is a multimodal clinical study that aims to elucidate the pathophysiology of chronic pain in knee osteoarthritis using advanced imaging methods. We will collect structural, neurochemical, psychological and sensory data to study this pain. Our primary aim is to analyze neurochemical concentrations in pain-processing centers of the brain in people with and without knee osteoarthritis from 40-75 years old. These data will also be collected following knee replacement at 3- and 6-month follow-ups.